Long term clinical outcome and bleeding complications among hospital survivors with acute coronary syndromes. Issue 965 (3rd March 2006) - Wong, P; Robinson, A; Shaw, S; Rodrigues, E
Abstract : Objective: To examine the 21 month clinical outcome and bleeding complications in hospital survivors with non-ST segment elevation acute coronary syndromes (NSTEACS) who were discharged with combined clopidogrel and aspirin anti-thrombotic therapy, and compare with those having ST segment elevation myocardial infarction (STEMI) who were discharged with aspirin alone. Design: Observational study. Setting: A large university hospital. Patients: 224 patients were admitted to hospital with either NSTEACS or STEMI, and survived to discharge between 1 October 2001 and 31 December 2002. Main outcome measures: Cardiovascular death, total death, new myocardial infarction, unstable angina requiring hospitalisation, stroke or transient ischaemic attack, coronary revascularisation; and fatal, life threatening, major and minor bleeding over 21 months after discharge. Results: Despite having no or small infarct (median maximum creatine kinase 155 v 1295 u/l; p<0.001) and taking more antianginal drugs, patients with NSTEACS had similar rates of cardiovascular death (9.5% v 8.3%; p = NS), new myocardial infarction (9.5% v 6.5%; p = NS) or unstable angina requiring hospitalisation (15.5% v 10.2%; p = NS) when compared with STEMI. Fatal, life threatening or major bleeding were <1% in both groups (p = NS); and minor bleeding occurred in 4.3% NSTEACS and 2.8% STEMI patients respectively (p = NS). Conclusions: Patients with NSTEACS had a similar and unfavourable long term outcome when compared with STEMI. There was no difference in serious bleeding complications between both groups.